Schellings Wesensbestimmung des Christentums in den Vorlesungen über die Methode des akademischen Studiums - Danz, Christian (HTS teologiese studies, 2007)
Schelling’s notion of the essence of Christianity according to his lectures on scientific methodology This article focuses on Schelling’s lectures on scientific method-ology, published in 1802. In these Vorlesungen Schelling developed his theory about the essence of Christianity against the background of a “philosopy of identity”. The article consists of three sections which investigate Schelling’s understanding of Christianity’s historical position in the academia. Theology as the science of Christian religion constitutes the essence of Christianity. The article aims to argue that Schelling’s understanding of theology as the object matter of philosophy should be seen in light of his view on Christianity’s historical position.